Plastidial Expression Of 3 Beta-Hydroxysteroid Dehydrogenase And Progesterone 5 Beta-Reductase Genes Confer Enhanced Salt Tolerance In Tobacco - Sameeullah, Muhammad; Yildirim, Muhammet; Aslam, Noreen; Baloglu, Mehmet Cengiz; Yucesan, Buhara; Loessl, Andreas G.; Saba, Kiran; Waheed, Mohammad Tahir; Gurel, Ekrem (Aperta, 2021)
The short-chain dehydrogenase/reductase (SDR) gene family is widely distributed in all kingdoms of life. The SDR genes, 3 beta-hydroxysteroid dehydrogenase (3 beta-HSD) and progesterone 5-beta-reductases (P5 beta R1, P5 beta R2) play a crucial role in cardenolide biosynthesis pathway in the Digitalis species. However, their role in plant stress, especially in salinity stress management, remains unexplored. In the present study, transplastomic tobacco plants were developed by inserting the 3 beta-HSD, P5 beta R1 and P5 beta R2 genes. The integration of transgenes in plastomes, copy number and transgene expression at transcript and protein level in transplastomic plants were confirmed by PCR, end-to-end PCR, qRT-PCR and Western blot analysis, respectively. Subcellular localization analysis showed that 3 beta-HSD and P5 beta R1 are cytoplasmic, and P5 beta R2 is tonoplast-localized. Transplastomic lines showed enhanced growth in terms of biomass and chlorophyll content compared to wild type (WT) under 300 mM salt stress. Under salt stress, transplastomic lines remained greener without negative impact on shoot or root growth compared to the WT. The salt-tolerant transplastomic lines exhibited enhanced levels of a series of metabolites (sucrose, glutamate, glutamine and proline) under control and NaCl stress. Furthermore, a lower Na+/K+ ratio in transplastomic lines was also observed. The salt tolerance, mediated by plastidial expression of the 3 beta-HSD, P5 beta R1 and P5 beta R2 genes, could be due to the involvement in the upregulation of nitrogen assimilation, osmolytes as well as lower Na+/K+ ratio. Taken together, the plastid-based expression of the SDR genes leading to enhanced salt tolerance, which opens a window for developing saline-tolerant plants via plastid genetic engineering.
Keywords: 2. Zero hunger